Islamic Financial Literacy in Sharia and Capitalist Economic Perspectives - Sahril; Abidin, Zaenal; Murtadho (CV. Zabags Qu Publish, 2026)
Islamic cooperatives serve as microfinance institutions that aim to integrate Islamic ethical values into financial practices, particularly in rural areas where access to formal banking remains limited. This study investigates the implementation of sharia principles in the savings and loan products of the Amanah Umat Cooperative in Dendang District, with a focus on the application of mudhārabah and musyārakah contracts. Utilizing a qualitative case study approach, the research involved field observations, in-depth interviews, and document analysis to capture the experiences of cooperative members and staff. The results show that while the cooperative demonstrates an intention to adhere to Islamic principles such as justice, mutual cooperation, and the prohibition of riba its implementation is constrained by informal practices, limited literacy, and the absence of internal sharia supervision. The use of mudhārabah and musyārakah is frequently inconsistent with normative sharia standards due to lack of contract clarity and risk-sharing mechanisms. This study contributes both theoretically and practically by offering grounded insights into the challenges of operationalizing Islamic finance at the grassroots level and highlights the need for context-sensitive strategies to enhance sharia compliance in cooperative systems.